Oral Cancer: how long does it take from Detection of a Lesion to the Beginning of Treatment - Costa, Edna Gonçalves da (2001)
The objective of the present study was to determine the time it takes from the detection of a malignant oral lesion until the moment treatment in a specialized center begins. Fifteen consecutive patients (9 males and 6 females) with malignant oral lesions who had been referred for diagnosis to the University of São Paulo School of Dentistry (FOUSP) were followed. No changes were made in the school’s routine management protocol. After one year of follow-up, we observed that patients waited a mean of 19.3 days to receive a diagnosis of the oral lesion, and waited 65.7 days until the beginning of treatment. Patients had to wait a mean of 84 days between the time of the first visit at FOUSP and the beginning of treatment. Based on the fact that early diagnosis of oral cancer and immediate treatment are important in the control of this disease leading to decreased morbidity and mortality we propose a re-evaluation of the protocol for the management of oral cancer patients at FOUSP.